Thoughts on Bleaching Guidelines. Issue 1 (2nd January 2017) - Brückle, Irene; Henniges, Ute
Abstract : Bleaching in paper conservation is a complex, highly invasive treatment that involves decisions regarding cultural, aesthetic, technical and scientific parameters. We present an overview of key requirements of bleaching that can be considered a basis for future standards and guidelines. In this context, we look at the function of standards and guidelines as regulatory documents supporting decision-making and quality control in complex professions where material and immaterial values factor into decision-making. Furthermore, a bleaching case involving light and hydrogen peroxide steps exemplifies the often neglected but essential treatment skill expertise in choosing and adjusting steps continually in response to the object's requirements. Bleaching treatment is argued to be part of scientific practice when it is conducted on the grounds of current professional knowledge and is reflected systematically so that it can contribute experiential knowledge to this practice.